Children Use Non-referential Gestures in Narrative Speech to Mark Discourse Elements Which Update Common Ground - Rohrer, Patrick Louis; Florit-Pons, Júlia; Vilà-Giménez, Ingrid; Prieto, Pilar (Frontiers in Psychology, 2022)
While recent studies have claimed that non-referential gestures (i.e., gestures that do not visually represent any semantic content in speech) are used to mark discourse-new and/or -accessible referents as well as focused information in adult speech, to our knowledge no prior investigation has studied the relationship between information structure and gesture referentiality in children’s narrative speech from a developmental perspective. A longitudinal database consisting of 332 narratives performed by 83 children at two different time points in development was coded for information structure and gesture referentiality (i.e., referential and non-referential gestures). Results revealed that at both time points, both referential and non-referential gestures were produced more with information that moves discourse forward (i.e., focus) and predication (i.e., comment) rather than topical or background information. Further, at 7-9 years of age, children tended to use more non-referential gestures to mark focus and comment constituents than referential gestures. Also, the results indicated that at both time points, both referential and non-referential gestures were produced more with predication (i.e., comment) and information that moves discourse forward (i.e., focus) rather than topical or background information. Further, at 7-9 years of age, children tended to use more non-referential gestures to mark comment and focus constituents than referential gestures. All in all, our findings offer supporting evidence that in contrast with referential gestures, non-referential gestures have been found to play a key role in marking IS, and that the development of this relationship solidifies at a period in development that coincides with a spurt in non-referential gesture production.